Ethnomusicology in East Africa. Perspectives from Uganda and Beyond. Selected papers from the 1st International Symposium on Ethnomusicology, Makerere University, Kampala, 2009. S. Nannyonga-Tamusuza and T. Solomon (eds.). 2012. Kampala: Fountain Publishers. 255pp. - Tracey, Andrew (International Library of African Music, 2012)
pages: 189
Keywords: Ethnomusicology; African Music; Uganda